The Effect of Discounts, Free Shipping, Online Customer Reviews on Purchasing Decisions at the Shopee Marketplace (Case Study on Students of Universitas Muhammadiyah Bengkulu) - Resa Yestasari; Mimi Kurnia Nengsih (Penerbit Jurnal Indonesia, 2024)
This research aims to determine